Analisis Inovasi dan Teknologi dalam Layanan Rawat Jalan Rumah Sakit Mata pada Masa Pandemi COVID-19 - Andreasih, Chika; Dhamanti, Inge (Jurnal Kesehatan Komunitas, 2024)
ABSTRACT The pandemic has had an impact on efforts to provide services at eye hospitals. The implications are related to services with the role of outpatient service preparedness and technological innovation. Objective: By Knowing the various management of outpatient services in eye hospitals during the COVID-19 pandemic, it is hoped that it can help increase patient safety rates and reduce the occurrence of errors in handling COVID-19. Method: The method used in the research is a literature review. Article searches use keywords, namely "eye hospital" and "outpatient" and "innovation" or "service" and "COVID-19". This reference is based on two database sources, namely Google Scholar and Science Direct in the last 5-year publication period (2019-2023). Selection of literature sources is carried out based on inclusion and exclusion criteria, source credibility, and relevance to the topic being discussed. Using this method, 173 selected literatures were selected resulting in 5 selected literatures. Results: From the selected literature, several innovations and technologies were found that can be used for services in eye hospitals during the pandemic, starting from the use of patient self-registration platforms, long-distance treatment, examinations with a combination of video and face-to-face consultations, telehealth and ride-hailing services -hailing, as well as teleophthalmology services with video consultation during the pandemic. The application of innovation and technology has proven to be effective and has had a positive impact on services at eye hospitals. Conclusion: Adjusting conditions and using technology to provide services to patients in eye hospitals during the pandemic can be done by using self-registration platforms, telemedicine, combined video and face-to-face consultation examinations, telemedicine-based services, and teleophthalmology video consultation services.